El Perro con Sombrero: A Bilingual Doggy Tale - Kent, Derek Taylor; Henry, Jed; Lugo, Gabriela Revilla (New York Henry Holt and Company, 2015)
Although Pepe achieves fame and fortune as a movie star dog--much to the chagrin of a jealous movie star cat--Pepe longs for a family.
Keywords: Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Motion picture actors and actresses -- Juvenile fiction; Pet adoption -- Juvenile fiction; Dogs -- Fiction; Cats -- Fiction; Actors and actresses -- Fiction; Pet adoption -- Fiction; Spanish language materials -- Bilingual